Program participation intensity and children's nutritional status: Evidence from a randomized control trial in Mozambique - de Brauw, Alan; Eozenou, Patrick; Moursi, Mourad (International Food Policy Research Institute, 2015)
Agricultural interventions are thought to have the potential to improve nutrition, but very little rigorous evidence is available about programs that link the two. In this paper, we study the nutritional impacts of Reaching End Users, a biofortification project in Mozambique that had integrated agricultural and nutritional components. We provide evidence on the dietary impacts of the program, but more importantly we study the impacts of the program by participation intensity. Using ordinary least squares and instrumental variables techniques, we find that more intense participation in both the agricultural and the nutritional components led to larger impacts. Therefore, the results could have important implications for refining the design of future projects that attempt to link agricultural and nutritional interventions.